2020
DOI: 10.1101/2020.08.04.237388
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impairment of the Hif-1α regulatory pathway in Foxn1-deficient (Foxn1−/−) mice affects the skin wound healing process

Abstract: Hypoxia and hypoxia-regulated factors [hypoxia-inducible factor-1α (Hif-1α), factor inhibiting Hif-1α (Fih-1)] have essential roles in skin wound healing. Using Foxn1-/- mice that can heal skin injuries in a unique scar-free manner, we investigated the interaction between Foxn1 and hypoxia-regulated factors. Foxn1-/- mice displayed impairments in the regulation of Hif-1α and Fih-1 during the healing process. An analysis of wounded skin showed that the skin of Foxn1-/- mice healed in a scarless manner, displayi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(18 citation statements)
references
References 73 publications
(119 reference statements)
5
13
0
Order By: Relevance
“…Based on the functional protein association network (STRING database; see Figure 3), which indicated that Foxn1 strongly activates the redox system, we showed that Txn and Txnrd together with detoxification proteins/detox proteins, for example, Nqo1 (quinone dehydrogenase NAD[P]H1), Glrx5 and Sxrn1, form an antioxidant defense coherent system. The results of in vivo experiments from our previous 45 and present study showed that cytosolic isoforms of the Txn system, Txn1, and Txnrd1 are increased in noninjured and injured skin of the Foxn1 +/+ but not Foxn1 −/− mice. However, overexpression of Foxn1 in keratinocytes as well as hypoxic culture conditions did not affect the mRNA or protein levels of Txn1 or Txnrd1 in vitro, suggesting wide‐ranging action of Foxn1 in the skin beyond keratinocytes.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Based on the functional protein association network (STRING database; see Figure 3), which indicated that Foxn1 strongly activates the redox system, we showed that Txn and Txnrd together with detoxification proteins/detox proteins, for example, Nqo1 (quinone dehydrogenase NAD[P]H1), Glrx5 and Sxrn1, form an antioxidant defense coherent system. The results of in vivo experiments from our previous 45 and present study showed that cytosolic isoforms of the Txn system, Txn1, and Txnrd1 are increased in noninjured and injured skin of the Foxn1 +/+ but not Foxn1 −/− mice. However, overexpression of Foxn1 in keratinocytes as well as hypoxic culture conditions did not affect the mRNA or protein levels of Txn1 or Txnrd1 in vitro, suggesting wide‐ranging action of Foxn1 in the skin beyond keratinocytes.…”
Section: Discussionsupporting
confidence: 64%
“…25 Using an in vitro and in vivo approach, we confirmed the increase in Ep300 mRNA expression in the Ad-Foxn1-stimulated keratinocytes as well as in the wounded skin of the Foxn1 +/+ mice. These results strongly correlate with the high levels of Hif-1α expression in the skin of Foxn1 +/+ mice, 45 indicating the possible role of Foxn1 and hypoxia in Hif-1α transcription through Ep300 activation.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations